Bioactivities, biosynthesis and biotechnological production of phenolic acids in Salvia miltiorrhiza. Issue 6 (26th March 2019) - Shi, Min; Huang, Fenfen; Deng, Changping; Wang, Yao; Kai, Guoyin
ABSTRACT: Salvia miltiorrhiza (Danshen in Chinese), is a well-known traditional Chinese medicinal plant, which is used as not only human medicine but also health-promotion food. Danshen has been extensively used for the treatment of various cardiovascular and cerebrovascular diseases. As a major group of bioactive constituents from S. miltiorrhiza, water-soluble phenolic acids such as salvianolic acid B possessed good bioactivities including antioxidant, anti-inflammatory, anti-cancer and other health-promoting activities. It is of significance to improve the production of phenolic acids by modern biotechnology approaches to meet the increasing market demand. Significant progresses have been made in understanding the biosynthetic pathway and regulation mechanism of phenolic acids in S.miltiorrhiza, which will facilitate the process of targeted metabolic engineering or synthetic biology. Furthermore, multiple biotechnology methods such as in vitro culture, elicitation, hairy roots, endophytic fungi and bioreactors have been also used to obtain pharmaceutically active phenolic acids from S. miltiorrhiza . In this review, recent advances in bioactivities, biosynthetic pathway and biotechnological production of phenolic acid ingredients were summarized and future prospective was also discussed.